2011
DOI: 10.1021/nl1042006
|View full text |Cite
|
Sign up to set email alerts
|

Silica-Coated Gold Nanorods as Photoacoustic Signal Nanoamplifiers

Abstract: Photoacoustic signal generation by metal nanoparticles relies on the efficient conversion of light to heat, its transfer to the environment and the production of pressure transients. In this study we demonstrate that a dielectric shell has a strong influence on the amplitude of the generated photoacoustic signal, and that silica coated gold nanorods of the same optical density are capable of producing about 3-fold higher photoacoustic signals than nanorods without silica coating. Spectrophotometry measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
473
0
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 480 publications
(487 citation statements)
references
References 58 publications
10
473
0
4
Order By: Relevance
“…However, other important clinical applications of the combined IVUS/ IVPA imaging are detection of the lipid-rich atherosclerotic plaques and visualization of molecular/cellular events within atherosclerotic plaques using nanoparticle-or dye-based contrast agents with unique molecular/cellular targeting and light absorption properties. 15,40,41 The combined IVUS/IVPA imaging of lipids has been successfully demonstrated at the wavelengths 1210 nm 13,19 and at 1720 nm 28 where the optical absorption coefficient of lipid exceeds that of water. 42 Combined IVUS/ IVPA imaging of ex vivo lipid-rich plaques in the presence of whole blood in the forward imaging mode 4 and using integrated IVUS/IVPA imaging catheter 28 has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…However, other important clinical applications of the combined IVUS/ IVPA imaging are detection of the lipid-rich atherosclerotic plaques and visualization of molecular/cellular events within atherosclerotic plaques using nanoparticle-or dye-based contrast agents with unique molecular/cellular targeting and light absorption properties. 15,40,41 The combined IVUS/IVPA imaging of lipids has been successfully demonstrated at the wavelengths 1210 nm 13,19 and at 1720 nm 28 where the optical absorption coefficient of lipid exceeds that of water. 42 Combined IVUS/ IVPA imaging of ex vivo lipid-rich plaques in the presence of whole blood in the forward imaging mode 4 and using integrated IVUS/IVPA imaging catheter 28 has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of the aspect ratio enables the tuning of the SPR of the resulting nanorods, which has led to multiplexing applications [321,324,326,327,344] . The gold nanorods are also effective as tracers for noninvasive in vivo spectroscopic photoacoustic SLN mapping in a rat model [350] .…”
Section: Gold-based Nanomaterialsmentioning
confidence: 99%
“…When they are silica-coated, the gold nanorods show increased photoacoustic [344] and photothermal stability and retain their superior optical properties under much higher fluences [323,325] when compared to PEG-coated gold nanorods, which implies better imaging capabilities and make silica-coated gold nanorods a promising imaging and therapeutic nano-agent for PAI and image-guided photothermal therapy. A recent paper reported the use of silica-coated gold nanorods in PAI for the quantitation of mesenchymal stem cells (MSCs) in rodent muscle tissue.…”
Section: Gold-based Nanomaterialsmentioning
confidence: 99%
“…Agarwal et al [46] demonstrated the ability of PAT for early detection of prostate cancer. Chen et al [47] found that silica coatings on GNRs can increase the signal to noise ratio of PAT compared with uncoated GNRs.…”
Section: Biomedical Imaging Of Gnrsmentioning
confidence: 99%